El sacrificio en el occidente de la Hispania Romana: Para un nuevo análisis de los ritos de tradición indoeuropea (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The current paper suggests a new analysis for the testimonies of the animal sacrifice and the sacrifice of men and horses in the western Roman Hispania, according to the perspective of compared religions, in the context of the Indo-European tradition. There lays the effort of defining clearly what we can really know and with what can we count on to proceed the investigation in these dominions.